Pengaruh Analisa Teknikal, Analisa Fundamental, Analisa Bandarmology Terhadap Profit Investor (Studi Kasus Saham Jakarta Islamic index Sektor Properti dan Real Estate yang Terdaftar Di Bursa Efek Indonesia Tahun 2018-2020) - Kevin Awaldza Ardhianto; Muhammad Mansur; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2022)
Abstract The current high inflation rate and low yields on banking products make people have to be smart in managing their finances so that the value of money does not shrink when spent. Investment instruments in stocks that already exist in the Financial Services Authority (OJK) regulations are an alternative choice for managing finances. This study is a quantitative study using secondary data in the form of technical analysis and bandarmological analysis obtained from the stock trading facility of one of the securities companies in Indonesia. Meanwhile, the stocks studied are JII (Jakarta Islamic Index) stocks for the 2018-2020 periode. Based on the research made, conducting technical analysis, fundamental analysis and bandarmology analysis simultaneously can provide higher profits for stock investors than if doing technical analysis, fundamental analysis and partial bandarmological analysis. Keywords: Technical Analysis, Fundamentals, Bandarmology, Investor profit